Effetiveness of Internal Audit in Tanzania Commercial Banks - Kisoka, Ireneo John (2011)
This study aimed to examine weather internal audit resources and competencies, internal audit activities i.e. the level of involvement of internal auditors in risk management activities together with the internal audit department level of interaction with audit committees has a significant impact on the level of internal audit effectiveness in the Tanzania commercial banks,keeping in mind that this function is now a mandatory requirement as per the Banking and Financial Institutions Act 2006.The results suggested that internal auditing in Tanzania commercial banks is still embracing traditional approach to internal auditing which is primarily concerned with compliance and monitoring rather than a value added approach to internal auditing. Although the Banking and Financial Institution Act (2006) explicitly requires risk management and corporate governance activities to be carried out by internal auditors in commercial banks, the results of this study deliberate that, there is no evidence to state that the risks management and corporate governance related activities of internal auditors are incorporated as value added activities as compared to mere regulatory fulfillments.